Implementasi Pendidikan Karakter Kedisiplinan Siswa di SD Negeri Kliteran Yogyakarta - Irfan Adi Nugroho (LP2M Universitas Sarjanawiyata Tamansiswa, 2020)
Character education is intensively carried out in the world of education today, can not be separated from character education in Indonesia. Character education is inseparable from the role of parents for the home environment, the role of teachers in the school environment, character education is emphasized in all education ranging from play groups to higher education. This article deals with the problem of how character education is embedded, as well as the character of how the character of discipline is applied.This article contains qualitative research, using the interview method and the observation method. The interview involved 7 respondents, consisting of 2 class IV students, 2 class V. students involved 2 teachers, class IV teacher and class V teacher and the principal. As for the observations seen in class IV and class V.the results of interviews and observations found that, in Kliteran Public Elementary School, character education was implemented, character education was implemented that was sponsored by student discipline. Both the principal has several rules so that students can set the rules well, can get prizes and decisions when violated. Classroom learning also applies the same thing, as conveyed by class IV and V teachers as resource persons in this article.